Global Burden and Mortality Trends of Thoracic Trauma: An Analysis Based on World Health Organization Data - Mohamad Rizki (CV. AFDIFAL MAJU BERKAH, 2026)
Trauma remains a leading cause of global mortality and disability, with thoracic trauma representing a critical subset due to its involvement of vital organs and high risk of fatal complications. Despite its clinical significance, comprehensive global assessments focusing specifically on thoracic trauma are limited, particularly those examining disparities across regions and income levels. This study aimed to analyze the global burden and mortality trends of thoracic trauma using World Health Organization (WHO) data, with a focus on regional and economic disparities. Methods: A cross-sectional secondary data analysis was conducted using publicly available datasets from the WHO Global Health Estimates, WHO Injury and Violence Prevention databases, and Global Burden of Disease (GBD) results integrated within WHO reports. Variables analyzed included the incidence and mortality of thoracic trauma, regional distribution based on WHO regions, and comparisons across World Bank income classifications. Thoracic trauma was defined according to WHO injury classifications. Data were analyzed descriptively and presented as absolute numbers, population-based rates where available, and comparative trends across regions and income groups. Results: The analysis demonstrated that thoracic trauma remains a major contributor to global injury-related mortality, with substantial disparities between high-income countries and low- and middle-income countries (LMICs). Mortality rates were disproportionately higher in LMICs despite comparable or lower injury incidence, indicating that system-level factors such as limited prehospital care, delayed diagnosis, and restricted access to definitive thoracic surgery play a central role in adverse outcomes. Conclusion: Thoracic trauma represents a significant and inequitable global health burden. Strengthening trauma care systems, particularly in LMICs, is essential to reducing preventable mortality. WHO-based global data provide valuable evidence to support policy development, resource allocation, and targeted interventions aimed at improving trauma outcomes worldwide